Assembly Requirements and Role of CotH during Spore Coat Formation in Bacillus subtilis - Zilhão, R. (American Society for Microbiology, 1999)
We report Western blot data showing that the 42.8-kDa product of the previously characterized cotH locus (8) is a structural component of the Bacillus subtilis spore coat. We show that the assembly of CotH requires both CotE and GerE. In agreement with these observations, the ultrastructural analysis of purified spores suggests that CotH is needed for proper formation of both inner and outer layers of the coat.